Development of Primary Student Emotional Quotient Based on Trisikkha under the Srisaket Primary Educational Service Area Office 1 - Sappasri, Kanyupha; Bamrungphak, Sowit; Vajirapanno, Phramaha Doasayam; Buarabha, Homhuan (Dhammathas Academic Journal, 2019)
The purposes of this study were 1) to study the emotional quotient (EQ) and Trisikkha principle of Buddhism; 2) to analyse the development of emotional quotient based on Trisikkha; 3) to present the development of primary student emotional quotient based on Trisikkha under the Srisaket primary educational service area office 1. The population targets were the forty-five students who were investigated the emotional quotient at T-Score Norms less than 49 (n = 45). The specific tools of this research were composed of 1) activities in the development of emotional quotient of the canon, concentration and wisdom; 2) the emotional quotient evalution form in 6-11 years old student of the department of mental health, ministry of public health. The data were analysed by using means, standard deviation and percentage, then they were presented by the descriptive analysis. The purposes of this study were 1) to study the emotional quotient (EQ) and Trisikkha principle of Buddhism; 2) to analyse the development of emotional quotient based on Trisikkha; 3) to present the development of primary student emotional quotient based on Trisikkha under the Srisaket primary educational service area office 1. The population targets were the forty-five students who were investigated the emotional quotient at T-Score Norms less than 49 (n = 45). The specific tools of this research were composed of 1) activities in the development of emotional quotient of the canon, concentration and wisdom; 2) the emotional quotient evalution form in 6-11 years old student of the department of mental health, ministry of public health. The data were analysed by using means, standard deviation and percentage, then they were presented by the descriptive analysis. The results of research were as follows: Emotional quotient (EQ) and principle of Trisikkha in Buddhism mention that the emotion means information of sense data or objectives of sensation at eyes, ears, nose, tongue, body and mind. Those are influenced to their behaviors, that show and respond to stimulus via sense or outer courtyard (Sense-fields) in Buddhism. It had the effects tocharacteristics of suffering (Wethnā) or the co-operative feeling to response from emotion or external stimuli to behaviors and sensation. Trisikkha means three sikkha that mention to topic of the study, the practice of those topics and self-practices of three topics. There are Adhisila-Sikkha that they study of canon (Sil), good practice to Adhicitta-Sikkha (study about mind, practice mind to peace and sustain to the high level of concentration and Adhipañña-Sikkha (study of self wisdom and develop self practice in good maner). The development of emotion quotient following principle of Trisikkha are the process of sensation in emotion. There are five steps; 1) Perception or Phạss'a of three objects that they are internal sense-fields (Ajjhattikāyanata), external sense-fields (Bhāhirāyatana) and spiratual (Consuosuness) 2) Suffering or Wethnā of perception of emotion after the contaction of Phạss'a 3) San-ya or memory of the information that it follows from suffering. This step is the accumulation of learning. 4) The modification of emotion or suffers (Wethnā) that is Sạngkhār, means thinking in mind. It has the power that can motivate the mind to good thinking (Wholesome), bad thinking (Unwholesome) and not good, not bad thinking (the indetermunate). This step is analyzed and modified information from memory or perception to craving or needs. 5) Analyzed and synthesized emotion is the last step of collection all information from all sensation to develop into wisdom or Pạnỵā. The effects of development of primary student emotional quotient based on the threefold traning under the Srisaket Primary Educational Service area office Ishowed the development of emotional quotient in canon (the preecpts). The students had good behaviors in keeping their disciplines, speaking, mind, responsibilities, charities and complete in learning and maturation in their emotion. Finally, they showed the development in wisdom (Pạnỵā). They had good development of intentions and skills in thinking. They also developed the good characteristics of all purpose objectives in learning. The examination of Ordinary National Educational Test (O-NET) at year 2016 in the primary students showed high scores in all subjects and increased the efficiency in their studies and learning.